An economic analysis of global oilseed market trends and demand dynamics - K Sivakumar; S Alexzander (Journal of Oilseed Brassica, 2025)
The global market for oil seeds, encompassing key crops such as soybeans, sunflower, canola, groundnut, mustard, castor, coconut (copra) and palm kernels, has witnessed remarkable growth over recent decades. This expansion is fuelled by rising population levels, increasing disposable incomes, and shifting dietary preferences towards healthier food options. Additionally, the versatile use of oil seeds in biofuel production has further augmented demand, aligning with global efforts to reduce reliance on fossil fuels and combat climate change. This study aims to analyse the intricate patterns of production, consumption, and trade that characterize the oil seeds market. By examining geopolitical influences, trade policies, technological advancements, and climate variability, we provide a comprehensive overview of the factors shaping market dynamics. Understanding these trends is essential for stakeholders across the supply chain, enabling them to navigate challenges and capitalize on emerging opportunities within this critical agricultural sector.